2017
DOI: 10.24908/pceea.v0i0.6509
|View full text |Cite
|
Sign up to set email alerts
|

Designing Rubrics to Assess Engineering Design, Professional Practice, and Communication Over Three Years of Study

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…In a review of literature on task-level formative feedback, Shute suggested that for most students, feedback with higher levels of specificity but lower complexity resulted in improved learning. However, characteristics of the learner are of importance to the impact feedback [6]. Our experiences also suggest that the characteristics of the learner or student are of importance.…”
Section: Formative Feedbackmentioning
confidence: 79%
See 4 more Smart Citations
“…In a review of literature on task-level formative feedback, Shute suggested that for most students, feedback with higher levels of specificity but lower complexity resulted in improved learning. However, characteristics of the learner are of importance to the impact feedback [6]. Our experiences also suggest that the characteristics of the learner or student are of importance.…”
Section: Formative Feedbackmentioning
confidence: 79%
“…Formative feedback can be categorized as general summary feedback or task-level feedback [8]. Both categories of formative feedback are used in the courses in the form of written feedback and the use of the rubrics outlined in [6]. In our experience, the combination of the grader and LA roles allows for higher quality task-level feedback.…”
Section: Formative Feedbackmentioning
confidence: 99%
See 3 more Smart Citations